PENGARUH PROFESIONALSIME GURU DAN MOTIVASI KERJA TERHADAP KINERJA GURU - dewi, citra (Pendidikan Administrasi Perkantoran FKIP Univesitas Sebelas Maret, 2014)
ABSTRACT The aims of this study were: (1) to find out whether there was any significant effect of teachers? professionalism to the teachers? performance of Batik Senior High School 2 Surakarta; (2) to find out whether there was any significant effect of work motivation to the teachers? performance of Batik Senior High School 2 Surakarta; and (3) to find out whether there was any significant effect of teachers? professionalism and work motivation to the teachers? performance of Batik Senior High School 2 Surakarta.This study used quantitative study approach, by descriptive method. The population of this study was all teachers of Batik Senior High School 2 Surakarta. Sampling technique used in this study was probability sampling that was simple random sampling by using raffling, in the amount of 35 students from a population of 55 teachers. The data collecting technique used was questionnaire and documentation techniques. While the data analysis technique of this study was statistical test by correlation analysis and multiple regression.Based on the result of this study, it could be concluded that: (1) there was a significant effect of teachers? professionalism to the teachers? performance of Batik Senior High School 2 Surakarta. It was shown by the value of rvalued > rtable or 0.443>0.334 on a significance level 5%; (2) there was a significant effect of work motivation to the teachers? performance of Batik Senior High School 2 Surakarta. It was shown by the value of rvalued > rtable or 0.634>0.334 on a significance level 5%; (3) There was a significant effect of teachers? professionalism and work motivation simultaneously to the teachers performance of Batik Senior High School 2 Surakarta. It was shown by Fvalued > Ftable or 22.528>3.295 on a significance level 5%. Other finding in this study was a multiple linear regression equation ? = -5.978 + 5.82X1 + 7.66X2, which meant that the average of teachers? performance would increased or decreased 5.82 on the increase of decrease of a teachers? professionalism unit, and would get 7.66X2 increase or decrease on the increase of decrease of a work motivation unit. Whereas the relative contribution of teachers? professionalism to the teachers? performance was 40.79%, and the relative contribution of work motivation to the teachers? performance was 59.21%. The effective contribution of teachers? professionalism to the teachers? performance was 23.85% and the effective contribution of work motivation to the teacher?s performance was 34.62%. Keywords: Teachers? professionalism, Work motivation, Teachers? performance